Variations in students’ experience of networked learning in a post-compulsory pre-university context - Cutajar, Maria; Zenios, Maria (Proceedings of the International Conference on Networked Learning, 2012)
This small-scale study used a phenomenographic approach to investigate variations in the experience of networked learning in a Maltese post-secondary educational context where students read a two-year academic programme of studies in preparation of tertiary level education. This research looked at an eight-week blended networked learning course which was specifically designed and implemented as an integral part of the pre-university programme and involved students who studied computing at an intermediate level. As an exploratory study, the research aimed at gaining insight into the different ways students experience networked learning. This research came after earlier research work revealed significant indifference among students to proposed online interactive and collaborative learning activities. Data was collected through five audio-recorded interviews held in Maltese with individual students. The interviews were translated to English after transcription and sent to students for any preferred amendments and approval. In an attempt to maximise variation with a limited number of participants, a purposive sample was chosen on the basis of students’ online activity during the networked learning course. Qualitative analysis of accumulated data suggested three distinct experiences tentatively labelled the ‘connected experience’, the ‘strategic experience’, and the ‘disconnected experience’, reflecting online participative attitude, perceived value in the learning approach, and readiness to take control directing personal learning activities. Brought together into a single hierarchical arrangement these three experiences are considered to form an outcome space in phenomenographic terms depicting variation in students’ experience of networked learning. This study is to be considered as work-in-progress on students’ experience of networked learning. Different experiences of NL suggest different perceptions of the value and worthiness of online discursive and collaborative activities for learning and consequently different levels of engagement in learning activities using different kinds of networked technologies. This pilot research study is considered to have opened a research route to deepen understanding of post-secondary Maltese students’ experience of networked learning. Given the potential of this learning paradigm for improving teaching and learning, such research may serve to stimulate interest, open conversations, and prompt initiative among local practitioners to explore ways how to effectively use available technologies for enhancing and augmenting teaching and learning in context.